Evaluation of Disk Halo Size and Identification of Correlated Factors in Myopic Adults - Zhao, Wuxiao; Zhao, Jing; Han, Tian; Li, Meng; Wang, Jifang; Zhou, Xingtao (Frontiers in Medicine, 2022)
This study aimed to evaluate glare source-induced disk halo size and assess its correlation with higher-order aberrations (HOAs), pupillometry findings, and contrast sensitivity in myopic adults (aged 23.8 ± 4.4 years). In this cross-sectional study, 150 eyes of 150 patients were assessed. All patients underwent routine ophthalmic examinations, wavefront aberrometry, halo size measurement, dynamic pupillometry, and contrast sensitivity tests. Spearman’s correlation analysis and independent sample t-tests were performed for data analysis. The mean halo radius was 82.5 ± 21.8 and 236.7 ± 52.2 arc min at 5 and 1 cd/m2 luminance levels, respectively. The values were inversely correlated with internal spherical aberration (SA) (r = −0.175, p = 0.032 and r = −0.241, p = 0.003, respectively), but not correlated with spherical equivalent (SE, both p > 0.05). Positive correlations were observed between halo radius and pupil size, contraction amplitude, and dilation speed during pupillary light reflex. Halo radii at 5 and 1 cd/m2 luminance levels were not significantly correlated with the area under the log contrast sensitivity function (r = −0.093, p = 0.258 and r = −0.149, p = 0.069, respectively). The mean halo radius was not clinically different between myopic and healthy eyes at 5 cd/m2 luminance level and did not differ significantly between the high and low-to-moderate myopia at 5 and 1 cd/m2 luminance levels (all p > 0.05). According to a stepwise linear regression model, the internal SA had a negative effect on the halo radius under low photpic condition; the average pupil diameter, internal SA and corneal HOAs played a large role in determining the halo radius under mesopic condition.